Factors Related to Premenstrual Syndrome in Young Women at MTsN Labuhanbatu in 2024 - Jolyarni, Novica; Nadrah, Nailatun; Nasution, Fitriyani (International Journal of Public Health Excellence (IJPHE), 2024)
Premenstrual syndrome (PMS) is a complex and poorly understood condition consisting of one or more of a number of physical and psychological symptoms that begin in the luteal phase of the menstrual cycle. World Health Organization (WHO) in 2020 PMS has a higher prevalence in Asian countries compared to western countries. The purpose of this study was to determine the factors associated with Premenstrual syndrome in adolescent girls at MTsN 1 Labuhanbatu in 2024. This research design uses an analytic survey, namely research trying to explore how and why the phenomenon occurs. Then analyze the dynamics of the correlation between phenomena, both between related factors (Indipendent) and effect factors (Dependent). The approach used in this research is cross sectional. The population in this study was 291 people. The sample in this study amounted to 74 people. Data analysis used univariate analysis and bivariate analysis using the chi-square test. The results of statistical tests with stress categories obtained using the chi-square test at a confidence level of 95% are known that psig 0.000 is smaller than 0.05, the results of chi-square tests with consumption patterns at a confidence level of 95% are known that psig 0.000 is smaller than 0.05, the results of statistical tests with premenstrual syndrome incidence obtained using the chi-square test at a confidence level of 95% are known that psig 0.000 is smaller than 0.05. In conclusion, it is known that there is a relationship between stress, consumption patterns and exercise with the incidence of premenstrual syndrome in adolescent girls at MTsN 1 Labuhanbatu in 2024. It is suggested that the results of this study can add insight, knowledge and experience about premenstrual syndrome that can occur at any time.